Didelio meistriškumo baidarininku aerobinis metabolizmas ivairaus intensyvumo darbe - Nekriošius, R.; Dadeliene, R. (Sporto Mokslas-Sport Science, 2020)
Purpose: to explore the changes of muscle oxygenation in high performance kayak athletes during competition and various intensity exercises.Methods: Two high performance kayak athletes participated in this study. The study was completed at the beginning of competition period, during three days restitution microcycle. Athletes` aerobic capacity and muscle oxygenation were determined. Exercise capacity and athlete heart rate were recorded. The concentration of lactate in the capillary blood was determined. Athletes performed five different physical exercises. Results and conclusions: The process of oxygenation was very intense during special exercise, in the muscles of the leg and chest of high performance kayak athletes. It depended on the intensity and duration of physical loads. When kayakers performed physical loads that were close to second ventilation anaerobic threshold, the oxygen in the leg muscles decreased less. Working at high intensity levels, oxygen level in leg muscles decreases even more than in the chest muscles. The study reveals the importance of leg muscles work, for kayakers working at very high power, close to critical intensity. It was observed that when kayakers performed repetitive exercises (6 times for 6 min at 220 W with rest for 6 min) and repeated repetitive exercises of the same volume (6 times worked after 6 min resting between sections for 6 min). However, during 6 min of work he performed physical work capacity at 320 W interval special exercise for 15 s and working lightly at 100 W for 45 s). The concentration of lactate in the capillary blood of the kayak athletes increased uniformly. Thus, with the aim of bringing the muscle control and physical load capacity of kayak athletes closer to the competitive level, it is appropriate to apply short high-intensity interval work. There is the scientific interest to apply such research to a wider contingent of athletes; it can bring practical benefits to the training of athletes.